Current Perspectives and Unmet Needs of Primary Immunodeficiency Care in Asia Pacific - Leung, Daniel; Chua, Gilbert T.; Mondragon, Alric V.; Zhong, Youjia; Nguyen-Ngoc-Quynh, Le; Imai, Kohsuke; Vignesh, Pandiarajan; Suratannon, Narissara; Mao, Huawei; Lee, Wen-I; Kim, Yae-Jean; Chan, Godfrey C. F.; et al. (Frontiers in Immunology, 2020)
Background: The Asia Pacific Society for Immunodeficiencies (APSID) conducted 9 primary immunodeficiency (PID) Schools in 5 years since inauguration to provide PID care training for early career physicians in Asia Pacific, a region with divergent needs in PID resources and training. Objective: To identify differences in PID patient care resource and training needs across Asia Pacific and propose a corresponding action plan. Methods: The Human Development Index (HDI) indicates the degree of socio-economic development in each country/region. Case abstracts and presenters’ personal statements from all Schools were analyzed. Diagnoses were categorized. Resource and training needs including depth of investigations expressed in testing levels, availability of genetic confirmation, and the origin of faculty members were analyzed. Results: 427 abstracts were received in 9 Schools between 2015 and 2020, predominantly on immunodeficiencies affecting cellular and humoral immunity. Genetic confirmation was described in 61.8% of abstracts. Essential immunological and genetic tests were not available in 25.4% and 29.5% of abstracts respectively, mainly from medium HDI countries/regions, which also had lower average testing levels. Cases from medium HDI countries/regions focused on learning how to investigate a patient for PIDs in cases of severe or atypical infections; whereas those from very high HDI countries/regions, from which most faculty members originated, listed hematopoietic stem cell transplantation and gene therapy, newborn screening and research as learning issues more frequently. Conclusion: There are unique HDI-related PID resource and training needs in each country/region. APSID proposes HDI group-specific strategies to improve PID care and education in her member countries/regions.